Evaluation of vermicompost on growth, yield and yield components of potato (Solanum tuberosum L.) in Debub Ari Woreda, Southwestern Ethiopia - Malla, Merdikios; Tesema , Genanaw; Hegano, Abebe (Journal of Science and Development, 2021)
Poor organic matter content along with soil fertility depletion due to the low amount of organic materials applied to the soil and complete removal of the biomass hinders crop production in Ethiopia. Therefore, the experiment was conducted to evaluate the vermicompost effect on the production of potatoes in Debub Ari district, southwestern Ethiopia. The experiment was conducted in the 2019 and 2020 main cropping seasons. Control, (69N+30P) kg ha-1, 3 t ha-1vermicompost, 4.5 t ha-1vermicompost, and (34.5N+15P) with 1.5 t ha-1vermicompost treatments were used for the experiment that laid out in RCBD following three replication with the spacing of 30cm and 75cm between plants and rows respectively. The full dose of vermicompost and inorganic fertilizers was applied at planting time. The result was revealed that application of 69N+30Pkgha-1 resulted in the highest total (47.18 t ha-1) and marketable (40.56 t ha-1) tuber yield which was statistically at par with response to application of 3 t ha-1 and 4.5 t ha-1 vermicompost, while the lowest total (29.99 t ha-1) and marketable (26.46 t ha-1) tuber yield were recorded from the nil. However, soil health and fertility improvement were influenced by the application of 3 t ha-1 and 4.5 t ha-1vermicompost. Application of 3 t ha-1vermicompost resulted in the highest marginal return of 4854.19% and improves soil health and fertility over the application of inorganic fertilizer alone and control. Therefore, the application of 3 t ha-1vermicompost was recommended for the study area and similar agro-ecologies. Further investigation should be done on its rate, tuber nutritional value and quality, and over the location.